Paroxysmal nocturnal haemoglobinuria a rare haematological disorder - literature review and case report - Rabbani, Mohammad Golam; Rahman, Jalilur; Chowdhury, MA Wahhab; Afrose, Salma; Rahman, Mahbubur (Journal of Chittagong Medical College Teachers' Association, 2009)
doi: 10.3329/jcmcta.v18i2.3838 Journal of Chittagong Medical College Teachers' Association 2007: 18(2):49-52